KEBERLANJUTAN DALAM KETERAMPILAN BARISTA: MONITOR DAN EVALUASI DARI PENGETAHUAN BARISTA TERHADAP KOPI SPESIAL DI THE COFFEE LAB DUBAI 2021 - Kurniawan Arif Maspul (STIE Atma Bhakti, 2021)
Abstract The number of coffee shops today is inseparable from the third wave in the coffee supply chain, especially the growth of specialty coffee in recent times. Sustainability is a key goal for all sectors, including supply chain soldering standards in coffee shops. Many Baristas don't understand the importance of sustainability in coffee shops and their management. To improve sustainability so that it aligns with ethical business skills and behavior, it is important to apply continuing education to the concept of Baristas thinking, understand their philosophy as coffee makers and connect all stakeholders in the coffee supply chain with consumers who need this information. This curriculum is delivered together with additional coaching, assessment, and interviews at the end of the activity to measure the knowledge of the Barista. The current object for this research is the Barista at The Coffee Lab Dubai, United Arab Emirates. The results give a positive value, where the effectiveness of the curriculum assessment results implemented through this counseling service has a very good impact where all Baristas pass the assessment, with the average practice exam assessment for all Baristas is 87.08, while the total average for the written exam is 84.42. From the interviews conducted with Baristas, most of the Baristas said that further knowledge through